Screening Patients Undergoing Total Hip or Knee Arthroplasty with Perioperative Urinalysis and the Effect of a Practice Change on Antimicrobial Use. (21st November 2016) - Bailin, Samuel; Noiseux, Nicolas; Pottinger, Jean M.; Johannsson, Birgir; Haleem, Ambar; Johnson, Sarah; Herwaldt, Loreen A.
Abstract : OBJECTIVE: To identify predictors of treatment for urinary tract infections (UTI) among patients undergoing total hip (THA) or knee (TKA) arthroplasties and to assess an intervention based on these predictors. DESIGN: We conducted a retrospective cohort study of 200 consecutive patients undergoing THA/TKA between February 21, 2011, and June 30, 2011, to identify predictors of treatment for UTI and a prospective cohort study of 50 patients undergoing these procedures between May 21, 2012, and July 17, 2012, to assess the association of signs or symptoms and UTI treatment. We then conducted a before-and-after study to assess whether implementing an intervention affected the frequency of treatment for UTI before or after THA/TKA. SETTING: The orthopedics department of a university health center. PATIENTS: Patients undergoing THA or TKA. INTERVENTION: Surgeons revised their UTI screening and treatment practices. RESULTS: Positive leukocyte esterase ( P <.0001; P <.0001) and urine white blood cell count>5 ( P =.01; P =.01) were associated with preoperative or postoperative UTI treatment. In the prospective study, 12 patients (24%) had signs and symptoms consistent with UTI. The number of patients treated for presumed UTI decreased 80.2% after the surgeons changed their practices, and surgical site infection (SSI) rates, including prosthetic joint infections (PJIs), did not increase. CONCLUSIONS: Urine leukocyte esterase and white blood cell count were the strongest predictors of treatment for UTI before or after THA/TKA. The intervention was associated with a significant decrease in treatment for UTI, and SSI/PJI rates did not increase. Infect Control Hosp Epidemiol 2017;38:281–286